MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI MODEL COLLABORATIVE TEAMWORK LEARNING PADA MATERI HIDROKARBON DI KELAS X 3 SMA NEGERI 12 BANJARMASIN - Raihanah Raihanah; Parham Saadi; Iriani Bakti (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract. This study aims to know increasing teacher activity, student activity, cognitive and affective learning outcomes, and students response. This study used a classroom action research design (CAR) and each cycles consisting of planning, action, observation and evaluation, analysis and reflection. The subjects of this study were students of X 3 SMA Negeri 12 Banjarmasin with 28 people. Research instruments are test and non test. Data were analysis by quantitative and qualitative analysis. The results showed that there was an increase of teacher activity from 47,67 (active enough) in cycle I to 52,83 (active) in cycle II, student activity increase from 37,57 (less active) in cycle I to 42,93 (active enough) in cycle II, cognitive learning outcomes increase from 68,56 (less) in cycle I to 81,03 (good enough) in cylcle II. There was an increase student affective learning outcomes from 9,02 (good enough) in cycle I to 10,48 (good) in cycle II. Student give positive response to learning by using collaborative teamwork learning model on hydrocarbons material. Keywords: learning outcomes, collaborative teamwork learning model, hydrocarbons